(untitled) (Medical Forum Monthly, 2023)
Objective: To assess the types of Optic Nerve (ON) in relation to sphenoid sinus in a subset of Karachi population using computed tomography. Study Design: Cross- sectional study Place and Duration of Study: This study was conducted at the Department of Radiology, Ziauddin Hospital Clifton campus from January to May 2017. Methods: We included a total of 270 participants (both genders) in this study. The study participants were between 21 to 60 years of age. CT scans were done using 16 slice Toshiba Alexion CT scanner. After gaining sequential axial images, volume data was created. Multiplanar reconstructions were made in all three planes namely sagittal, axial and coronal. Three-dimensional volume image construction was done in bone algorithm. ON was assessed according to DeLano’s classification. Results: On the right-side, type 1 Optic Nerve was observed most frequently in both genders with frequency of 53.31% in males and 60.9% in females. This was followed by type III and type III Optic Nerve whereas, type IV was found to be least frequent in both genders. Similar pattern was observed on the left side where type I Optic Nerve was most commonly observed in both genders while type IV was found to be least common with a frequency of 5.63% in males and 8.18% in females. There was insignificant difference in the frequencies of the types of optic nerve among gender on right side. (p = 0.251). Similarly, the p value on left side between the gender was also found to be insignificant (P= 0.542). Conclusion: Type II and type III optic nerve are associated with increased chances of nerve injury these two types were observed with frequency of 37.96% on both sides in our study which indicates increased chances of nerve injury during surgery.